Penerapan ISAK No 35 dan Good Governance pada Laporan Keuangan Nonlaba - Dinda Audina; Gatot Wahyu Nugroho (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study examines the implementation of ISAK No. 35 and good governance principles in non-profit financial statements, focusing on Pesantren Kaligrafi Al-Qur'an Lemka. Using a qualitative approach with interviews and document analysis, the research reveals that the pesantren has not fully implemented ISAK No. 35 due to limited awareness and resources. However, it demonstrates efforts to apply good governance principles, particularly in transparency and accountability. The study identifies challenges in consistent real-time recording and the absence of written financial management guidelines. Recommendations include enhancing understanding of ISAK No. 35, developing written guidelines, and improving technological utilization for financial management.